019 The national headache management system: a route to ensuring nationwide evidence-based and equitable care. Issue 9 (12th August 2022) - Gordon, Alex; Lashley, Daniel; Weatherby, Stuart
Abstract : Headache disorders are one of the three most common reasons for presentations to neurology services. Despite this, quality of headache care is known to be highly variable. Over 50% of patients have never received prophylactic medication despite eligibility, and patient concordance with treatment is poor. The national headache management system, a freely available resource via headache.org.uk, is an addition to the British Association for the Study of Headache (BASH) 2019 guidelines. It allows both patients and clinicians to view material on diagnostic and treatment strategies in a systematic and logical way. The system can benefit patient care by (1) improving likelihood of response to treatment due to evidence based recommendation, (2) increasing headache service efficiency through the potential for greater multidisciplinary professional use in the running of services, and (3) improving patient confidence, and therefore concordance with, treatment through a uniform approach to headache. The headache management system thus represents an easy-to-use tool which has the potential to bring about huge improvements to headache care on a nationwide scale. Further iterations of this system include development of an app patients can use to track their care, with any problems signposting them to the appropriate advice via the website.